GARDENING AND MELON GROWING IN THE SYSTEM OF ECONOMIC ACTIVITY OF THE POPULATION OF PLAIN AND SUAMONTANE DAGESTAN IN THE XVIII-FIRST HALF OF THE XIX CENTURIES. - Aliev, Bagomed Gadaevic (History, Archeology and Ethnography of the Caucasus, 2016)
The article presents the first study of the state of gardening and melon growing in plain and submontane Dagestan as a whole. On the basis of available sources the author makes an attempt to ascertain the areas of gardening and melon growing and to display their place in the system of economic activity and importance for economic life of population  in 18th – the firgt half of the 19th century.
Keywords: gardening and melon growing; Derbent and Derbent domein; Salataviya; Mekhtulin domein